Pengaruh kebijakan fiskal Amerika, nilai tukar, dan rezim nilai tukar terhadap pertumbuhan ekonomi Indonesia - Fitri, Amelia; Putro, Tri Sukirno; ', Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Integrated in the world economy and open, then the policy conducted by a state against the country’s economy could have an impact on other countries. The impact of policy and economic activity is transmitted through international trade of a country to another country. The larger the economic size of a country, the greater the effect on other countries, either directly or indirectly. Economic impact is also determined by the amount of international trade in economic activity that occurred between contries. Greater international economic activity, the greater the external impact on the domestic economy. This study aims examine the effect of American fiscal policy in terms of the American budget deficit, exchange rate, and the exchange rate regime on Indonesian economic growth. This research uses secondary data. Analysis method used is desciptive quantitative, the error correction model (ECM) analysis using Eviews 7.0 program. The research that has been conducted, the overall significant effect of independent variables on the dependent variable. Individually, the American budget defisit and the exchange rate are both positively related and do not significantly affect on Indonesian economic growth. While the exchange rate regime, negatively related and significantly affect on Indonesian economic growth.Keywords : Indonesian economic growth, American budget deficit, exchange rate, exchange rate regime, Eror Correction Model (ECM).